2017
DOI: 10.1111/sum.12352
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a DUALEM‐421 and inversion modelling to map baseline soil salinity along toposequences in the Hunter Valley Wine district

Abstract: In the oldest commercial wine district of Australia, the Hunter Valley, there is the threat of soil salinization because marine sediments underlie the area. To understand the risk requires information about the spatial distribution of soil properties. Electromagnetic (EM) induction instruments have been used to identify and map the spatial variation of average soil salinity to a certain depth. However, soils vary with depth dependent on soil forming factors. We collected data from a single‐frequency and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…σ can be correlated using linear regression (LR) with measured EC e at any depth. For example, Stockmann, Huang, Minasny, and Triantafilis (2017) showed how such an LR could be used to predict dryland EC e down a catenary sequence in the Hunter Valley, Australia. A similar approach was used to calibrate and map EC e across a small alluvial-estuarine area influenced by acid sulfate soil (Goff, Huang, Wong, Monteiro Santos, & Triantafilis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…σ can be correlated using linear regression (LR) with measured EC e at any depth. For example, Stockmann, Huang, Minasny, and Triantafilis (2017) showed how such an LR could be used to predict dryland EC e down a catenary sequence in the Hunter Valley, Australia. A similar approach was used to calibrate and map EC e across a small alluvial-estuarine area influenced by acid sulfate soil (Goff, Huang, Wong, Monteiro Santos, & Triantafilis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, methods and techniques have been shown to be capable of accounting for this vertical change through the use of EM inversion software. In 2‐D, this includes the development of electromagnetic conductivity images (EMCI) to map salinity associated with gilgai landscapes (Huang, Mokhtari, Cohen, Monteiro Santos, & Triantafilis, ), across an alluvial–estuarine area (Goff, Huang, Wong, Monteiro Santos, Wege, & Triantafilis, ) and down a toposequence (Stockmann, Huang, Minasny, & Triantifilis, ). In 3‐D, salinity has also been mapped using EMCI within a field affected by dryland salinity (Huang, Kilminster, Barrett‐lennard, & Triantifilis, ) and in an irrigated field (Zare, Huang, Monteiro Santos, & Triantafilis, ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the intercept (4.1253) of their calibration was much larger than herein, where the range in EC e was much smaller (0–10.31 dS m −1 ). Interestingly, Stockmann et al (2017) found that while the intercept (−0.079; 0.046 × σ − 0.079) was equivalent to the one herein the slope (0.046) was almost three times larger for the calibration between EC e and σ estimated from inversion of DUALEM‐421 EC a measured down a catenary sequence in the nearby Hunter Valley and on duplex soil types. We attribute this to the more highly weathered nature of the clays, which characterise the Australian Soil Orders (i.e., Kurosols, Chromosols and Dermosols) of the Pokolbin Soil Landscape (Kovac & Lawrie, 1991) and derived from parent rocks of Permian age (e.g., mudstones).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EC e has been mapped for average rootzone or discrete depths. Recently, DUALEM-421 data (Stockmann et al, 2017) or using two instruments (EM38 and EM31) in concert (Triantafilis & Monteiro Santos, 2010), have been inverted to true electrical conductivity (σ, mS m −1 ) at various depths using a quasi-two dimensional (Q-2D) inversion software (EM4Soil, EMTOMO, 2014); where σ has been directly correlated to EC e at the same depths, to develop a LR calibration. Most recently, Zare et al (2015) showed that using a quasi-three dimensional (Q-3D) inversion of DUALEM-421 and EM34 could be employed to map soil EC e adjacent to a large water reservoir.…”
Section: Introductionmentioning
confidence: 99%